(3JhGdi GdJCfjS HeYGdi GHf EOQjSs - (3CMeO Hf Ydj Hf eMeO Hf MLQ GdTGaYj GdcfGfj GdYSbdGfj, TgGH GdOjf CHh GdaVd, GHf MLQ, J (B852 (3g` s ((3ecI GdecQeI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd fLhe GdSeGA gOGjI ddMjGQi ai GdHQ hGdHMQ ef GdXdeGA s
(3BNQgG (B:s
(3BNQ GdJQLeI GdeHGQcI GdeJYdbI HGdEeGe GdTGaYi GdeSeGI HJhGdi GdJCfjS HeYGdi GHf COQjS s
(3HChdgG SeGY GdSNGhi dgPG GdcJGH Ydi eDdag hGLGRJg (B[ (3GdSNGhi (B] (3dHYVge SfI (B897s
(3aQZ GdeDda ef JCdjag SfI (B835s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
Keywords: (3GdMOjK h GdeUWdMs